Intrahepatic Cholestasis of Pregnancy and Transaminitis in Women with COVID-19: A Case Series - Anne R. Waldrop; Andrea Henkel; Kelley B. Lee; Maurice L. Druzin; Natali Aziz; Yasser El-Sayed; Deirdre J. Lyell (Thieme Medical Publishers, Inc., 2024)
Objective The four initial severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-infected pregnant women presenting at term gestation to our institution presented with transaminitis. Three of the four were diagnosed with intrahepatic cholestasis of pregnancy (IHCP). Growing evidence exists of an associated transaminitis in nonpregnant SARS-CoV-2 patients. However, there are limited data of hepatic involvement of SARS-CoV-2 in pregnancy, and no previous studies have assessed the association with IHCP in patients with coronavirus disease 2019 (COVID-19).